The immanent transcendence of negative utopia : Adorno sul Finale di partita di Beckett - Magno, Emanuela (Scenari, 2021)
First of all the essay aims to shed light on the fact that Adorno’s entire aesthetic “discourse” refers to the dimension of transcendence. Its second purpose is to illustrate the way in which this is manifested in the inherent logic of the work of art. In the first part of the text, therefore, an attempt is made to clarify the role that the dialectic’s “negative” plays in Adorno’s conception of art, in order to show how this negativity becomes, in the work of art, the crucial device of an immanent transcendence in the work of art itself, in the name of utopia. In the second part the contribution turns back to the analysis that Adorno reserves for Beckett’s Endgame, an analysis that will allow us to grasp the meaning of the immanent transcendence of the negative utopia of art “on the field” of Beckett’s work.